Design and Analysis of a Novel Opposite Trapezoidal Flow Channel for Solid Oxide Electrolysis Cell Stack - Zhen Zhang; Chengzhi Guan; Leidong Xie; Jian-Qiang Wang (Energies, 2022)
High efficiency, raw material availability, and compatibility with downstream systems will enable the Solid Oxide Electrolysis Cell (SOEC) to play an important role in the future energy transition. However, the SOEC stack’s performance should be improved further by utilizing a novel flow-field design, and the channel shape is a key factor for enhancing gas transportation. To investigate the main effects of the novel channel design with fewer calculations, we assumed ideal gas laminar flows in the cathode channel. Furthermore, the cathode support layer thickness and electrical contact resistance are ignored. The conventional channel flow is validated first with mesh independence, and then the performance difference between the conventional and novel designs is analyzed using COMSOL Multiphysics. The process parameters such as velocity, pressure, current density, and mole concentration are compared between the conventional and novel designs, demonstrating that the novel design significantly improves electrolysis efficiency. Furthermore, it directly increased the concentration of product hydrogen in the novel channel. In addition to enhancing convection and diffusion of reaction gases in neighboring channels, the simple structure makes it easy to manufacture, which is advantageous for accelerating commercial use of the novel design.